Ethnomathematical Exploration of Belitung’s Typical Tambourine Musical Instrument - Pradhita Lestari, Novia; Mulyawati, Ima (Jurnal Indonesia Sosial Teknologi, 2024)
Exploring ethnomathematics is not only about understanding mathematical concepts in various cultures but also about appreciating the cultural heritage and local wisdom embodied in the understanding of mathematics of each culture. Ethnomathematical exploration can be used as a means of preserving a culture that is carried out through learning at school. One of these ways is to apply ethnomathematical concepts to learning. The relationship between mathematics education and ethnomathematics stems from recognizing that mathematics is not culturally neutral. The field of ethnomathematical studies aims to discover mathematical ideas inherent in different cultural groups. This study seeks to explain ethnomathematical concepts contained in typical Belitung tambourine musical instruments and how they are used to teach mathematics. In this study, researchers used qualitative methods and an ethnographic approach. Researchers collected data through interviews, observations, and documentation in this study. Where the results of this study state that there is a mathematical concept in the typical Belitung tambourine musical instrument. To introduce and understand mathematical concepts through local culture, they can be submitted through mathematical concepts in the standard Belitung tambourine musical instrument.